The Use of Cost-Benefit Analysis in Environmental Policy - Elizabeth F. Pienaar (EDIS)
When analyzing environmental problems, economists consider both the benefits and costs of actions. If benefits exceed costs then economic theory supports that action. For example, if the total benefits of conserving land exceed the costs then cost-benefit analysis would support conservation of the land. However, great care must be taken to accurately identify and quantify benefits and costs to determine whether an action is cost-benefit justified. Stakeholders may have an incentive to overstate costs or benefits, in order to influence decision-making. This 5-page fact sheet was written by Elizabeth F. Pienaar, and published by the UF Department of Wildlife Ecology and Conservation, September 2013. http://edis.ifas.ufl.edu/uw383